Effect of Pre-Slaughter Age on Carcass Traits and Chemical Composition of Mutton in Deccani Sheep - Pachpute, S.T.; Dak, E.G.; Nimase, R.G.; Bangar, Y.C.; Gadekar, Y. (Journal of Meat Science, 2016)
The aim of the present study was to study the effect of pre-slaughter age on carcass traits and chemical composition of mutton in Deccani sheep maintained at Network project on Sheep Improvement (Farm Based Unit), MPKV (Maharashtra) during the period of April, 2014 to June, 2015. Six Deccani lambs of 4, 5 and 6 months of age groups (two each) were selected randomly and slaughtered according to the common procedure under the federal inspection. The present study indicated that the empty weight, the dressing percentage on empty weight basis and loin eye area of lambs increased gradually with increase in age. The Chemical composition (protein, fat, and Cholesterol) of mutton of Deccani sheep was found to significantly (p
Keywords: Deccani; Sheep; Mutton; Chemical composition; Protein